Diseño e implementación de un sistema alarma de seguridad por dispositivo inalámbrico de envío y recepción de señal por módulos Xbee a la estación de Policía Nacional en Acevedo/Huila (2023)
The project proposal focuses on a problem in the municipality of Acevedo/Huila, due to the presence of public disturbances as a result of the growing invasion of lots near commercial areas. Merchants have stated that they cannot open their establishments due to threats of looting and robbery. According to the above, there is a need to implement a security alarm system by wireless device sending and receiving signal by Xbee modules to improve the timely response of the national police in the presence of public conflicts. Using a methodology of practical research type, which will allow to know the environment where the alarm system will be implemented, for its later application with 5 establishments and a reception point. The tests were performed at selected points over a maximum range of 300 meters from the police station, using five Xbee S1 modules of the Whip Antenna type and the same model for the receiver, reaching -86.4 dBm for a distance of 190 m, and from 220 m to 300 m there is intermittency in the signal strength.